Agama, Kekerasan dan Perlawanan Ideologis - Umi Sumbulah (Islamica: Jurnal Studi Keislaman, 2006)
Violence in the name of religion often occurs because of the ideologicalinterpretation of religion. Well-formulated ideology is obeyed by its followers to achievecertain goals. Ideology may also be appropriated by its proponents to rebel against thestatus quo that they think is not in line with their belief system. A closed-ideology thatperpetuates intolerance is a latent source of conflict and violence. In addition, manyreligion-oriented violence is associated not only with religion per se as a source of inspirationand legitimacy, but also with such factors as social, economic, political as well aspsychological conditions of human being. One-sided explanation of violence in the nameof religion is therefore insufficient as religion is not monolithic phenomenon.